1999
DOI: 10.1159/000045469
|View full text |Cite
|
Sign up to set email alerts
|

Increased Prevalence of Apolipoprotein E3/E4 Genotype among Swedish Renal Transplant Recipients

Abstract: There is increasing evidence that lipoproteins are involved in the progression of kidney diseases and in the deterioration of kidney transplant function, although the exact mechanism is still not known. Common polymorphisms of apolipoprotein E genotype associate with the variability of lipoprotein levels and composition. We have, therefore, determined the apolipoprotein E genotype in a group of 112 renal transplant patients, of whom 27 had had an episode of acute vascular rejection, while 85 had not. We found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…In fact, ESRD patients presented a lower frequency distributions of the e3 allele and the E3/E3 genotype and higher frequency distributions of the e4 allele and E3/E4 genotype than the controls. These results are in agreement with the findings in Caucasians and Swedish patients 20,21 and suggested that the e4 allele and E3E4 genotype are associated with ESRD. A weak association between the e4 allele and a low glomerular filtration rate was recently demonstrated.…”
Section: Discussionsupporting
confidence: 92%
“…In fact, ESRD patients presented a lower frequency distributions of the e3 allele and the E3/E3 genotype and higher frequency distributions of the e4 allele and E3/E4 genotype than the controls. These results are in agreement with the findings in Caucasians and Swedish patients 20,21 and suggested that the e4 allele and E3E4 genotype are associated with ESRD. A weak association between the e4 allele and a low glomerular filtration rate was recently demonstrated.…”
Section: Discussionsupporting
confidence: 92%
“…We too found that patients with apoE3/4 progressed significantly more quickly. Another study speculated that apoE3/4 was a specific risk factor for progression of renal failure requiring transplantation after finding a significantly higher frequency of apoE3/4 genotypes in the transplant recipients [24]. …”
Section: Discussionmentioning
confidence: 99%
“…This is true for the polymorphisms investigated in the current review. For example, Lahrach et al [ 21 ] showed that the e4 allele and the E3E4 genotype of the apoE gene demonstrated a strong association with ESRD, similar to a study conducted in a Swedish population [ 46 ]. However, a study conducted in African Americans and European Americans showed an opposite effect, with the e4 allele being associated with decreased risk of ESRD progression and decreased risk of prevalent ESRD [ 47 ], with no association found between the e4 allele and CKD in Asian populations [ 48 ].…”
Section: Discussionmentioning
confidence: 54%